The crucial role of epigenetic regulation in breast cancer anti-estrogen resistance: Current findings and future perspectives. (July 2022) - Sukocheva, Olga A.; Lukina, Elena; Friedemann, Markus; Menschikowski, Mario; Hagelgans, Albert; Aliev, Gjumrakch
Highlights: This review examines advances in the epigenetic regulation of endocrine drug resistance and anti-resistance strategies in breast cancers. The most influential breast cancer resistance-related mechanisms are regulated by epigenetic mechanisms. Estrogen receptor (ER) modifications, expression, and ER-triggered genes are controlled by specific epigenetic tools. ER promoter signalling can be modified by hypermethylation of CpG islands, increased histone deacetylase activity, and/or by miRNAs. Blockade of histone acetyltransferases (MYST3), deacetylases (HDAC1), and/or demethylases (LSD1) can re-sensitize to anti-estrogen effects. Abstract: Breast cancer (BC) cell de-sensitization to Tamoxifen (TAM) or other selective estrogen receptor (ER) modulators (SERM) is a complex process associated with BC heterogeneity and the transformation of ER signalling. The most influential resistance-related mechanisms include modifications in ER expression and gene regulation patterns. During TAM/SERM treatment, epigenetic mechanisms can effectively silence ER expression and facilitate the development of endocrine resistance. ER status is efficiently regulated by specific epigenetic tools including hypermethylation of CpG islands within ER promoters, increased histone deacetylase activity in the ER promoter, and/or translational repression by miRNAs. Over-methylation of the ER α gene ( ESR1 ) promoter by DNA methyltransferases was associated with poor prognosis and indicated the development of resistance. Moreover, BC progression and spreading were marked by transformed chromatin remodelling, post-translational histone modifications, and expression of specific miRNAs and/or long non-coding RNAs. Therefore, targeted inhibition of histone acetyltransferases (e.g. MYST3), deacetylases (e.g. HDAC1), and/or demethylases (e.g. lysine-specific demethylase LSD1) was shown to recover and increase BC sensitivity to anti-estrogens. Indicated as a powerful molecular instrument, the administration of epigenetic drugs can regain ER expression along with the activation of tumour suppressor genes, which can in turn prevent selection of resistant cells and cancer stem cell survival. This review examines recent advances in the epigenetic regulation of endocrine drug resistance and evaluates novel anti-resistance strategies. Underlying molecular mechanisms of epigenetic regulation will be discussed, emphasising the utilization of epigenetic enzymes and their inhibitors to re-program irresponsive BCs.